Simulation and Analysis of Motion Space of Spatial Series Mechanism of Two to Six Degrees of Freedom - Zang Hongbin (Jixie chuandong)
Aiming at spatial series mechanism used in the theory of mechanism,a motion space equation for a six- DOF is built by using the D- H homogeneous coordinate transformation. The virtual prototyping models are built from the two to six- DOF with the mechanical dynamics analysis software ADAMS. Based on the virtual prototyping technology,the motion spaces of spatial series mechanism from two to six- DOF are simulated and analyzed. The conditions for non- blind area are also given.